2017
DOI: 10.3389/fmicb.2017.00975
|View full text |Cite
|
Sign up to set email alerts
|

A Small Number of Low-abundance Bacteria Dominate Plant Species-specific Responses during Rhizosphere Colonization

Abstract: Plant growth can be affected by soil bacteria. In turn, plants are known to influence soil bacteria through rhizodeposits and changes in abiotic conditions. We aimed to quantify the phylotype richness and relative abundance of rhizosphere bacteria that are actually influenced in a plant species-specific manner and to determine the role of the disproportionately large diversity of low-abundance bacteria belonging to the rare biosphere (<0.1 relative abundance) in this process. In addition, we aimed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 73 publications
11
55
0
Order By: Relevance
“…Our results are important in the context of the increasing awareness that the microbial rare biosphere is not only the largest pool of biodiversity on Earth (1-4) but in sum of all its lowabundance members constitutes also a large part of the biomass in a given habitat (5,14).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our results are important in the context of the increasing awareness that the microbial rare biosphere is not only the largest pool of biodiversity on Earth (1-4) but in sum of all its lowabundance members constitutes also a large part of the biomass in a given habitat (5,14).…”
Section: Discussionmentioning
confidence: 86%
“…For example, in the studied peatland, the sum of all low-abundance species made up approximately 12% of the total bacterial and archaeal 16S rRNA genes (5). In other soils, low-abundance Alphaproteobacteria and Bacteroidetes alone constituted in sum 10% and 9% of the total bacterial population, respectively, while all low-abundance populations summed up to 37% of all bacteria (14). Upon strong environmental change, low-abundance microorganisms often grow to numerically abundant populations and replace dominant species as observed for microbial community changes after an oil spill (72, 73) or in the response of soil microorganisms towards the presence of plants (14).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Unfortunately, we know little about the contribution of these low abundant groups to overall gut homeostasis [179]; in fact, some researchers suggest and promote the removal of low abundant microbes from analysis in order to detect "true" phylotypes [180]. This is not a trivial topic, at least in other environments such as soil it has been shown that the low-abundance bacteria play a fundamental biological role [181] and may, in fact, be keystone species regulating the function of different microbial environments, including host-associated microbiomes [182].…”
Section: Why Is Akkermansia So Rare In the Digestive Tract Of Cats Anmentioning
confidence: 99%